Gatekeeping Process Dalam Citizen Journalism Berkaitan Dengan Partisipasi Masyarakat Dalam Masyarakat Dalam Menyampaikan Informasi Lalulintas di Radio Idola FM Semarang - Putri, Nora Prima Wardani (Jurnal The Messenger, 2012)
This research was made to gain the information how the gate keeping process in Idola Radio works in public journalism responds that give informations by telephone or sms to Idola Radio.This research base on the theory how the gate keeping process decides if the information proper or not to deliver into news and also the basic concept of citizen journalism that carry out by the people themselve who will give the information such as a reporter.The methods that use in this research are qualitative description and perspective interactive. This research was made in FM Idola Radio Semarang and the resource was the staff who may concern.From this research   can be take a conclusion than the gatekeeper   take   a role to classify the information from public who act by the Program Manager, news supervisor and reporters. The Gatekeeper is the main point in every broadcast. It has a big role to select every news or informations before they put on the broadcast room to be on air.